Project Report on Electronic Information Display Using Embedded System - JAFFER SAYEED, GAYATHRI R D, RINNI C S, SAVITHA and TABASSUM TAJ (2008)
INTERNAL GUIDE: ANIL RAAVI, MVJCE EXTERNAL GUIDE: SRIKANTH, DESIGN ENGINEER AIRCRAFT DIVISION HAL
Keywords: Electronic Information Display Using Embedded System